2013
DOI: 10.1103/physrevlett.111.111102
|View full text |Cite|
|
Sign up to set email alerts
|

Zwei-Dreibein Gravity: A Two-Frame-Field Model of 3D Massive Gravity

Abstract: We present a generally covariant and parity-invariant two-frame field ("zwei-dreibein") action for gravity in three space-time dimensions that propagates two massive spin-2 modes, unitarily, and we use Hamiltonian methods to confirm the absence of unphysical degrees of freedom. We show how zwei-dreibein gravity unifies previous "3D massive gravity" models and extends them, in the context of the AdS/CFT correspondence, to allow for a positive central charge consistent with bulk unitarity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 20 publications
3
90
0
Order By: Relevance
“…The particular staggering of partial derivative indices in the expression (32) is reproduced by exterior algebra from the compact expression (29). It is worth to emphasize that the expression (32) is the expression obtained by making use of the linearized Christoffel symbols and the linearized Riemann tensor and that (32) is merely the expression of (29) in component form.…”
Section: The Components Of the Linearized Einstein Tensor Can Now Be mentioning
confidence: 99%
“…The particular staggering of partial derivative indices in the expression (32) is reproduced by exterior algebra from the compact expression (29). It is worth to emphasize that the expression (32) is the expression obtained by making use of the linearized Christoffel symbols and the linearized Riemann tensor and that (32) is merely the expression of (29) in component form.…”
Section: The Components Of the Linearized Einstein Tensor Can Now Be mentioning
confidence: 99%
“…Very recently, a new 3D gravity model with very interesting properties, called ZweiDreibein Gravity (ZDG), was proposed [1]. It was shown in [18] that this bigravity theory can be viewed as a higher-derivative gravity theory of which NMG is a particular limit.…”
Section: Jhep09(2014)132mentioning
confidence: 99%
“…It was recently shown that this is the only asymptotatically Lifshitz black hole with z = 1 in the theory [23]. 1 The metric of this three-dimensional z = 3 Lifshitz black hole is given by the following line element…”
Section: Lifshitz Black Hole In Nmgmentioning
confidence: 99%
See 2 more Smart Citations